Applying the coral reefs optimization algorithm for solving unequal area facility layout problems - Garcia-Hernandez, L. (2020)
Coral Reefs Optimization (CRO) is a recently proposed evolutionary-type algorithm which has shown promising results to tackle many complex optimization problems. This paper discusses the performance of this meta-heuristic in Unequal Area Facility Layout Problems (UA-FLPs). The UA-FLP is an important problem in industrial production, which considers a rectangular region and a set of rectangular facilities. These facilities must be allocated in the plant in the most adequate way satisfying certain constraints. The Flexible Bay Structure has been selected in order to represent solutions for the UA-FLP in the proposed CRO algorithm. In this paper, we detail the implementation of the algorithm and provide the results of different tests in several UA-FLP instances with different size and setting. The obtained results confirm the excellent performance of the proposed algorithm in solving UA-FLPs, improving alternative algorithms devoted to this problem in the literature.